G6pd deficiency and haemolyticanaemia in urban heterogeneous population of bhopal - MANJU TIWARI,; DINESH PARMAR,; N.C. SHARMA, (International Journal of Pharma and Bio Sciences, 2017)
G6PD deficiency one of the most common enzyme deficiency disorder is associated with hemolysis of RBCs. Deficiency of the enzyme fails to impart protection against oxidative stress due to infection , therapy or dietary factors leading to hemolysis of RBCs. The Present study investigates the incidence of G6PD and correlates it to alterations in the Hemoglobin count and reticulocyte count non tribal, hospital visiting population of Bhopal. In the study patients visiting three hospital of Bhopal were analyzed for G6PD deficiency and standard tests for the detection of the deficiency and other tests like Reticulocyte count and Hemoglobin estimation were done for the purpose of correlation. The study found a significant difference in the incidence of disease between males & female. Moreover G6PD deficiency in patients also showed a significant covering of Hb and a significant increase in the reticulocyte count as compared to normal (control) subjects. The results of the present study were well in agreement with similar studies throughout the world. The study concludes a severe health hazard due to G6PD deficiency not only in tribal rural population but also in heterogeneous urban population of Bhopal which may be due to endogamy and tribal connection such groups.